Great inventions that changed the world - Wei, James, 1930- (Hoboken, NJ : Wiley, A John Wiley & Sons, Inc., 2012)
"This book is designed for a general audience, similar to those who would read Scientific American. The book describes how inventions arise from human needs instead of when the inventions were made or what technologies were involved. Chapter 1 introduces the world of inventions, and the common features of major inventions and inventors. Chapters 2 through 8 describe human needs and desires, and how inventions support them"--
Machine generated contents note: Foreword -- Preface -- Chapter 1. Introduction -- 1.1 Inventors and Inventions -- 1.2 Innovation, Development, Diffusion -- 1.3 Changing the World -- Chapter 2. Inventions for Work -- 2.1 Tools and Methods -- 2.2 Energy and Power -- 2.3 Materials -- Chapter 3. Domestic Life: Food, Clothes, House -- 3.1 Food -- 3.2 Clothes -- 3.3 House -- Chapter 4. Health, Reproduction -- 4.1 Prevention -- 4.2 Diagnostics -- 4.3 Therapy -- 4.4 Reproduction -- Chapter 5. Security -- 5.1 Nature Threats -- 5.2 Economic Threats -- 5.3 Human Violence, War -- Chapter 6. Transportation -- 6.1 Land Transportation -- 6.2 Water Transportation -- 6.3 Air and Space Transportation -- Chapter 7. Information -- 7.1 Observation -- 7.2 Records -- 7.3 Communication -- 7.4 Information Tools -- Chapter 8. Good Life -- 8.1 Party, Play -- 8.2 Luxury -- 8.3 Arts -- Chapter 9. Future Challenges -- 9.1 Future Needs and Opportunities -- 9.2 Future Sources of Inventions -- References -- Index.
Includes index.
"Written by one of the world's great engineers, this book provides the curious with an explanation of how inventions have developed from human needs and desires. Chapters discuss the impacts of inventions in our work, personal lives, societies, and the environment. The text also outlines what steps we need to take to ensure continued success of new inventions, and how to mange them wisely. Based on a Princeton University course for a general audience, this book lays out a means for understanding yesterday and today's inventions, and paves the way for tomorrow's innovations"--Provided by publisher.
Machine generated contents note: ForewardPrefaceChapter 1. Introduction1.1 Inventors and Inventions1.2 Innovation, Development, Diffusion1.3 Changing the WorldChapter 2. Inventions for Work2.1 Tools and Methods2.2 Energy and Power2.3 MaterialsChapter 3. Domestic Life: Food, Clothes, House3.1 Food3.2 Clothes3.3 HouseChapter 4. Health, Reproduction4.1 Prevention4.2 Diagnostics4.3 Therapy4.4 ReproductionChapter 5. Security5.1 Nature Threats5.2 Economic Threats5.3 Human Violence, WarChapter 6. Transportation6.1 Land Transportation6.2 Water Transportation6.3 Air and Space TransportationChapter 7. Information7.1 Observation7.2 Records7.3 Communication7.4 Information ToolsChapter 8. Good Life8.1 Party, Play8.2 Luxury8.3 ArtsChapter 9. Future Challenges9.1 Future Needs and Opportunities9.2 Future Sources of InventionsReferencesIndex.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Inventions; Technological innovations; TECHNOLOGY & ENGINEERING -- Engineering (General); Inventions; Technological innovations; Electronic books; Electronic books